Emotions in Europe, 1517-1914
1 online resource (1442 pages)
Keywords: This four-volume collection of primary sources focuses on the history of emotions in Europe and its empires between 1517 and 1914. Arranged chronologically, each volume examines the subjects of the self, family and community, religion, politics and law, science and philosophy, and art and culture. The collection begins with the Reformation in 1517 as a key transformative moment in European history that required people to rethink the self, belief, and scientific knowledges - all of which shaped and were shaped by emotion. It ends with WW1, by which point psychology and modern frameworks for the self had become standard knowledges. In between, ideas and practices of emotion were not static, and part of the history charted across these volumes is the making of a new vocabulary for emotions and the self. Sources include letters, diaries, legal papers, institutional records, newspapers, science and philosophical writings, literature and art from a diversity of voices and perspectives. Accompanied by extensive editorial commentary, this collection will be of great interest to students of history and literature.